2015
DOI: 10.1099/mic.0.083097-0
|View full text |Cite
|
Sign up to set email alerts
|

Absence of YbeY RNase compromises the growth and enhances the virulence plasmid gene expression of Yersinia enterocolitica O:3

Abstract: YbeY was recently recognized as an endoribonuclease playing a role in ribosome biosynthesis. In Escherichia coli it functions as a single-strand-specific RNase that processes the 39 end of the 16S rRNA and is crucial for the late-stage 70S ribosome quality control system. Here we report that YbeY is not essential in Yersinia enterocolitica serotype O:3, yet its absence strongly compromised the bacterium. The lack of YbeY resulted in misprocessing of 16S rRNA and a severe decrease of growth rate with complete g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 56 publications
(56 reference statements)
5
41
0
Order By: Relevance
“…In V. cholerae , YbeY is involved in pathogenesis, as its depletion leads to reduced colonization of mouse intestines and decreased cholera toxin production (2). Moreover, inactivation of YbeY was recently shown to impair many virulence-related features of Yersinia enterocolitica (10). Yet another striking example for YbeY’s central role in bacterial RNA metabolism is its association with apoptosis-like death (ALD) in E. coli in response to severe DNA damage, which—among other specific characteristics—also shows YbeY-dependent rRNA degradation (11).…”
Section: Introductionmentioning
confidence: 99%
“…In V. cholerae , YbeY is involved in pathogenesis, as its depletion leads to reduced colonization of mouse intestines and decreased cholera toxin production (2). Moreover, inactivation of YbeY was recently shown to impair many virulence-related features of Yersinia enterocolitica (10). Yet another striking example for YbeY’s central role in bacterial RNA metabolism is its association with apoptosis-like death (ALD) in E. coli in response to severe DNA damage, which—among other specific characteristics—also shows YbeY-dependent rRNA degradation (11).…”
Section: Introductionmentioning
confidence: 99%
“…A transcriptomic study designed to identify genes under the control of the recently recognized YbeY endonuclease demonstrated that deletion of the ybeY gene led to an upregulation of lcrF and the T3SS/yop genes in Y. enterocolitica serotype O:3 under conditions in which these genes are usually repressed (i.e., at 22°C) (76). This derepression was not caused by lower YmoA levels, since the amount of ymoA transcript was increased in the ybeY mutant.…”
Section: Ypstb Ypiii 598 Tcatttcttttctattagtggggtgcgctacccccccaatgccmentioning
confidence: 99%
“…This derepression was not caused by lower YmoA levels, since the amount of ymoA transcript was increased in the ybeY mutant. Instead, the authors suggested that lcrF upregulation in the ybeY mutant was due to increased copy numbers of the virulence plasmid or to altered regulation of global regulators (e.g., Hfq, nucleoid-structuring proteins) affecting the noncoding RNA network and/or DNA supercoiling (76).…”
Section: Ypstb Ypiii 598 Tcatttcttttctattagtggggtgcgctacccccccaatgccmentioning
confidence: 99%
“…Since the levels of Ysc/Yop transcripts and proteins were increased or remained unchanged in the absence of a functional PNPase or RNase E, they seem to influence transcription/mRNA decay and activity of the T3SS by distinct mechanisms [61]. Moreover, the single-strand specific RNase Y (YbeY) that processes the 3'-ends of the 16S rRNA and is responsible for the late-stage 70S ribosome quality control, also affects many virulence-related features, including acid stress resistance, cell adhesion/invasion properties and T3SS [62]. Among the YbeY-regulated ncRNAs are CsrB and CsrC of the global carbon starvation regulator system, which may explain the pleiotropic virulence-associated phenotypic changes of an ybeY mutant.…”
Section: Changing Mrna Half-livesmentioning
confidence: 99%